2022
DOI: 10.1186/s12889-021-12445-6
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led theoretically Desinged HIV/AIDS prevention intervention among students: a case of health belief model

Abstract: Background & aim HIV/AIDS is one of the most dangerous viruses known in the world. In addition, considering its fatality rate and high cost of care, it is a serious threat to the health and economy of social communities. Adolescents are one of the high-risk groups. One of the most effective ways to prevent this disease is to promote healthcare, raise awareness, and change health-related beliefs and attitudes. This study aims at determining the effect of peer education, based on the health b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The results of the study demonstrated that the designed intervention successfully reduced the average score of STIs Perceived cognitive barriers(fear) significantly after the educational intervention in the experiment group; Some of these study results are consistent with other research studies [ 55 57 ]. Both Sadeghi’s and Huang’s studies found a decrease in Perceived barriers among participants in the experimental group compared to the control group following the intervention [ 58 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the study demonstrated that the designed intervention successfully reduced the average score of STIs Perceived cognitive barriers(fear) significantly after the educational intervention in the experiment group; Some of these study results are consistent with other research studies [ 55 57 ]. Both Sadeghi’s and Huang’s studies found a decrease in Perceived barriers among participants in the experimental group compared to the control group following the intervention [ 58 ].…”
Section: Discussionsupporting
confidence: 87%
“…The results of the study by Varas-Díaz et al showed that participants in the intervention group had lower levels of Perceived social exclusion related to STIs compared to the control group [ 54 ]. Other studies have highlighted the positive role of family support and peer-based interventions in reducing perceived social exclusion by families [ 48 , 55 ]. The results of the present study suggest that women had high levels of perceived social exclusion related to STIs before the intervention, The designed intervention successfully reduced the average score of perceived social exclusion related to STIs among women in the experiment group after the educational intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Peer education centred on HBM, for instance, has been effectively used as an approach to encourage preventative behaviours amongst female students in Iran (Moshki, Zamani-Alavijeh, & Mojadam, 2017). On the same note, Joorbonyan, Ghaffari, and Rakhshanderou (2022) discovered that after an HBM that emphasized peer education, the intervention education could influence awareness level, susceptibility, degree of severity, advantages, perceived challenges, perceived confidence, behavioural intention, and ultimately avoidance of high-risk behaviour. This proves that the HBM is based on the notion that students are likely to change and cease their behaviour if they perceive they are at risk of acquiring disease and that preventing it will be helpful to them (Glanz, Rimer, & Viswanath, 2015).…”
Section: The Health Belief Modelmentioning
confidence: 99%
“…Adolescents often face emotional instability, significant physical and social changes, exploring their identities, and seeking validation within peer groups, which can influence their behaviors, including engaging in risky sexual activity and substance abuse, potentially exposing them to HIV/AIDS (Stanhope & Lancaster, 2015 ). Previous studies from Sub-Saharan Africa (Joorbonyan et al, 2022 ; Mwale & Muula, 2017 ; Siddiqui et al, 2020 ) have highlighted peer relationships’ influence on adolescents’ behavior, emphasizing the need for effective interventions to promote healthier lifestyles. Peer education has emerged as a promising approach to improve adolescents’ preventive and health behaviors so that they avoid risky sexual behavior and promote healthy sexual behavior among their peers (He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%